Genotoxicity of chemical compounds identification and assessment by yeast cells transformed With GFP reporter constructs regulated by the PLM2 or DIN7 promoter: $hVan Ngoc Bui, Thi Thu Huyen Nguyen, Yvan Bettarel, Thi Hoai Thu Nguyen, Thuy Linh Pham, Thi Yen Hoang, Vu Thanh Thanh Nguyen, Ngoc Minh Nghiem, and Stefan Wölfl - Van, Ngoc-Bui; Nguyen, Thi Thu Huyen; Bettarel, Yvan; Nguyen, Thi Hoai Thu; Pham, Thuy Linh; Hoang, Thi Yen; Nguyen, Vu Thanh Thanh; Nghiem, Ngoc Minh; Wölfl, Stefan (International journal of toxicology, 2015)
Yeast cells transformed with high-copy number plasmids comprising a green fluorescent protein (GFP)-encoding gene optimized for yeast under the control of the n...